Discourse theory trumps discourse theory: Wouter Hanegraaff's Esotericism and the Academy - Otto, Bernd-Christian (Religion, 2013)
This review article argues that Wouter Hanegraaff's Esotericism and the Academy is deeply influenced by a methodological cluster usually referred to as 'discourse theory.' That the author is not willing to classify his own approach as such is explained with recourse to his dispute with Kocku von Stuckrad, who, according to Hanegraaff, would embody discourse theory, whereas Hanegraaff would embody history. A comparison of Hanegraaff's Esotericism and the Academy: Rejected Knowledge in Western Culture (Cambridge: Cambridge University Press, 2012) and von Stuckrad's Locations of Knowledge in Medieval and Early Modern Europe: Esoteric Discourse and Western Identities (Leiden: Brill, 2010) reveals that this is a misleading classification and that Hanegraaff's study comes closer to what discourse theory is all about. As a consequence, Esotericism and the Academy is the very first study on 'Western esotericism' that offers a convincing justification of this particular label as an overarching discursive category. © 2013 Copyright Taylor and Francis Group, LLC.
Created from Fastlane, Scopus look-up
Keywords: discourse theory; European history of religions; Kocku von Stuckrad; Western esotericism; Wouter J. Hanegraaff